From Ethics to Refusal: Protecting Migrant and Refugee Students from the Researcher's Gaze - Gavilanes, Vianney (Refuge, 2022)
This piece makes a methodological contribution to refugee studies in the context of the “ethical turn” in the field by arguing for a spectre orientation to the student voice that resituates participant knowledge as diffused rather than explicit. This orientation, as a methodological stance, goes beyond reflexivity and practices a refusal to engage in damage-centred research. Drawing from a broad theoretical and conceptual literature within the contexts of forced migration, this short essay expands the current literature focusing on procedural ethics by offering a more humanizing methodology for conducting research with migrant and refugee youth during the COVID-19 pandemic.